PENGARUH TOTAL QUALITY MANAGEMENT DAN MANAJEMEN PENGETAHUAN TERHADAP KINERJA ORGANISASI - Ella Anastasya Sinambela; Didit Darmawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
Organizational management applies the right strategy to be able to remain competitive with other competing organizations. The implementation of the strategy is not only about the benefits but also the performance of the organization. Organizational performance is one of the successes in market business competition. Company management implements strategies that can develop organizational performance by developing supporting aspects such as TQM and knowledge management. This research was conducted to determine the formation of organizational performance from TQM and knowledge management. This research was conducted at a company in Sidoarjo which is engaged in the manufacture of animal feed. The respondents obtained were employees from different divisions who were randomly selected except for the security and cleanliness division. In this study used a sample of 120 respondents. The data used will be analyzed using multiple linear regression. After processing the data, the results showed that there was a significant influence given by TQM on organizational performance. Data processing also proves that organizational performance is formed because of the significant influence given by knowledge management. Research also proves that TQM and knowledge management have an effect on the ups and downs of organizational performance together.